On Treaties’ Designation - Vidin, Blagoy (Yearbook of the Law Department, 2019)
Under consideration in the paper is the issue regarding treaties’ designation. It is well accepted that the concrete treaty designation is not crucial for the treaty. The analysis of the state practice of Bulgaria reveals, that there is distinction between the various types of treaties and that the designation is part of that distinction.